PSYCHOANALYSIS, ETHICS AND INCLUSIVE EDUCATION - Lerner, Ana Beatriz Coutinho; Voltolini, Rinaldo (Nuances: estudos sobre Educação, 2016)
This paper aims to investigate the central ways in which the discourse on Inclusive Education assumes in contemporary times and some the effects of this discourse on the subjectivity of children, parents and school professionals. In order to accomplish this goal, we first review the literature concerning Inclusive Education, showing the origins of this movement, the main legal frameworks that organize this subject and the current theoretical perspectives. We then analyze discursive elements considering the notion of ethics in psychoanalysis formalized by Lacan in the Seminar, Book 7: The ethics of psychoanalysis and present some contributions that the notion can bring to Inclusive Education. http://dx.doi.org/10.14572/nuances.v26i2.3185